DNA profile of dog feces as evidence to solve a homicide - Barrientos, Laura Soledad (2016)
Dog fecal samples were collected at the crime scene and from the shoes of the suspectto see whether they could be linked. DNA was genotyped using a 145 bp fragmentcontaining a 60 bp hotspot region of the mitochondrial DNA (mtDNA) control region.Once the species origin was identified, sequences were aligned with the 23 caninehaplotypes defined, showing that evidence and reference had 100% identity withhaplotype 5. The frequency of haplotype 5 and the exclusion power of the referencepopulation were 0.056 and 0.89, respectively. The forensic index showed that it was 20times more likely that the evidence belonged to the reference dog than to some otherunknown animal. The results support that the mtDNA hypervariable region 1 (HV1) isa good alternative for typing in trace or degraded casework samples when the STRpanel fails, and demonstrate the utility of domestic animal samples to give additionalinformation to solve human legal cases.